FIFTY YEARS OF RESEARCH ON HUMAN SETTLEMENTS AND ITS IMPLEMENTATION IN INDONESIA - Sumintardja, Djauhari (Nalars, 2009)
ABSTRACT. This paper is attempted to discuss various research on human settlement programme in Indonesia either in reference to urban settlement or rural in the role of research that has been regarded as an important one. The range of issues and problem were like a long string stretched from designing a new town to urban kampong improvement; from building a communal toilet to simple water purification method; from gender issues to making soil blocks. The discussion of this paper will covered many range of issues as follow: research to build new satellite town for Jakarta, research in developing alternative building materials, appropriate technology in sanitation and water supply, research to support improvement of rural housing, and finally, research in connection with natural disasters. Keywords: human settlement, urban, rural ABSTRAK. Tulisan ini akan memaparkan berbagai macam studi penelitian tentang program permukiman di Indonesia baik dari sudut referensi pada permukiman perkotaan maupun permukiman pinggiran sebagai salah satu masalah yang terpenting pada penelitian ini. Berbagai isu dan masalah diangkat dari mulai bagaimana merencanakan sebuah kota baru sampai pada perbaikan kampong di perkotaan, dari mulai membangun kamar mandi umum sampai dengan metode purifikasi air yang sederhana, dari mulai isu gender sampai pada masalah pembuatan blok-blok tanah.   Penjelasan dari tulisan ini akan mencakup beberapa isu sebagai berikut: penelitian atas pembangunan kota satelit baru bagi Jakarta, penelitian dalam pengembangan material bangunan alternative, teknologi tepat guna dalam sanitasi dan suplai air, penelitian dalam mendukung peningkatan kualitas pada permukiman pinggiran dan terakhir akan membahas hubungan dengan bencana alam. Kata kunci: permukiman, perkotaan, pedesaan/ pinggiran